STUDI JANGKA PANJANG TENTANG EFEKTIVITAS INTERVENSI PSIKOLOGIS DALAM MENINGKATKAN KEMAMPUAN BELAJAR MANDIRI DAN PRESTASI BELAJAR MAHASISWA PENDIDIKAN JARAK JAUH - Tri Darmayanti; Murni Rachmatini; Firman Karim (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2011)
This research was conducted to trace the long effects of psychological interventions, which were provided in the previous research in 2004. The psychological interventions were given to the distance learners of Universitas Terbuka (UT) in the previous research experiments in 2004. The psychological treatments had been aimed to enhance self-directed learning abilities to the first year students of Public Administration Study Program of UT, who registered in 2004.The respondents had randomly assigned into three experimental groups and one control group. The learners achievement had been followed to the first semester of 2007 and 2008. Learnersachievement was measured through regular course examinations. The three experimental groups were tested against the control group. The hypothesis was tested using analysis of Variances (ANOVA). The results show that after a 3 to 4 yeras there was a significant difference in students achievement between the experimental groups and the control group (p = 0.027). In summary, this research proves that psychological interventions that are usually used in face-to-face education could effectively be used in distance education context as well. As the findings show that, after a period of time, the interventions significantly increase students awareness of the need to learn that leads to the increase in their self-directed learning abilities and their achievement.